Early but reversible haemostatic changes in a-symptomatic females expressing COVID-19 antibodies. Issue 217 (September 2022) - Williams, J.O.; Nash, J.; Whelan, C.; Raven, B.M.; Davies, A.J.; Evans, J.; Watkeys, L.; Morris, K.; James, P.E.
Abstract: The coronavirus, COVID-19 pandemic spread across the globe in 2020, with an initial high case mortality in those requiring intensive care treatment due to serious complication. A vaccine programme was quickly developed and currently the UK is one of highest double vaccinated and boosted countries in the world. Despite tremendous efforts by the UK, new cases of COVID-19 are still occurring, due to viral mutation. A major problem associated with COVID-19 is the large a-symptomatic spread within the population. Little investigation into the a-symptomatic population has been carried out and therefore we pose that the residual effects of a-symptomatic infection is still largely unknown. Prior to mass vaccination, a multi-phased single cohort study of IgM and IgG COVID-19 antibody prevalence and the associated haemostatic changes were assessed in a Welsh cohort of 739 participants, at three time points. Positive antibody participants with age and gender matched negative antibody controls were assessed at 0, 3 and 6 months. Antibody positive females appeared to have lower antibody responses in comparison to their a-symptomatic male counterparts. Despite this initial testing showed a unique significant increase in TRAP-6-induced platelet aggregation, prothrombin time (PT) and clot initiation time. Despite coagulation parameters beginning to return to normal at 3 months, significant decreases are observed in both haemoglobin and haematocrit levels. The production of extracellular vesicles (EV) was also determined in this study. Although the overall number of EV does not change throughout the study, at the initial 0 months' time point a significant increase in the percentage of circulating pro-coagulant platelet derived EV is seen, which does not appear to be related to the extent of platelet activation in the subject. We conclude that early, but reversible changes in haemostatic pathways within the a-symptomatic, female, antibody positive COVID-19 individuals are present. These changes may be key in identifying a period of pro-coagulative risk for a-symptomatic female patients.